Bibliotecarul și bucătăria lui: o abordare postumanistă - PILCHIN, Maria (BIBLIOPOLIS, 2025)
Kitchens in the buildings of public library, as an element of posthumanist and transhumanist philosophy, can be viewed from multiple perspectives: an ethics of care (counteracting chronic diseases and fast-food consumerism), on the one hand, and distancing from hierarchical management that lacks empathy for employees, on the other, etc. These spaces, typically dedicated to food, meal breaks, and socialization, can become symbols of the intersection between technology, humanity, and the future of knowledge and humankind in general. What do the kitchens in the branches of the B.P. Hasdeu Municipal Library signify for the librarian community? How can we interpret them through the lens of new currents in human thought?